2016
DOI: 10.1002/cjce.22593
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of ultrasonic radiation on growth kinetic of asphaltene aggregation and deposition

Abstract: Ultrasonic treatment as an economical and green technology has been much attended in petroleum industry, especially for inhibition and removal of asphaltene deposition in the near wellbore region. The performance of ultrasonic waves is affected by different parameters such as time, power, frequency, type of radiation, etc. In this communication, the effects of duration of ultrasonic radiation, power, and stability on asphaltene aggregation were evaluated from a kinetic point of view. In fact, the optimal radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Further evidence of the effect of ultrasound on organic scales is the visualization studies of the removal of asphaltene in porous media using 2D glass micromodel conducted at 20 kHz, 40 W [32] and at 30 kHz, 100 W [33]. The authors showed that ultrasound could significantly reduce the precipitation of asphaltene and prevent its deposition in porous media, howbeit over exposure of samples to ultrasound augmented the damage caused by asphaltenes [32]. The main mechanism of ultrasound contributing to the prevention of asphaltene deposition was found to be vibrations.…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediamentioning
confidence: 99%
“…Further evidence of the effect of ultrasound on organic scales is the visualization studies of the removal of asphaltene in porous media using 2D glass micromodel conducted at 20 kHz, 40 W [32] and at 30 kHz, 100 W [33]. The authors showed that ultrasound could significantly reduce the precipitation of asphaltene and prevent its deposition in porous media, howbeit over exposure of samples to ultrasound augmented the damage caused by asphaltenes [32]. The main mechanism of ultrasound contributing to the prevention of asphaltene deposition was found to be vibrations.…”
Section: Effect Of Ultrasound On Formation Damage In Porous Mediamentioning
confidence: 99%
“…The interaction between the asphaltene particles decreases with a decrease in their size, which subsequently leads to a decrease in viscosity. Thus, according to the conclusions made in work [10], cavitation efficiency is due to both local temperature increase in the area of cavitation bubbles collapse and the effect of cavitation directly on asphaltenes.…”
Section: Reduced Viscosity Of Crude Oil By Cavitationmentioning
confidence: 74%
“…There are works where ultrasonic treatment of oil and oil products is described at low power values: 20 W [15], 40 W [36], 10-60 W [31], 75 W [35], 100 W [37], and 150 W [38].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in work [36], all samples of light crude oil (20 mL) were exposed to ultrasonic treatment with the power of 40 W and duration up to 10 min. Optimum values of time and radiation power were 2.5 min and 40 W, respectively.…”
Section: Introductionmentioning
confidence: 99%